Building self-esteem by prosthetic rehabilitation in a child with hypohidrotic ectodermal dysplasia, role of pediatric dentist: A case report - Khatri, Amit; Kalra, Namita; Tyagi, Rishi; Garg, Neetu; Sabherwal, Puja; Sharma, Mayank (Indian Journal of Case Reports, 2022)
Ectodermal dysplasia (ED) is a congenital disorder exhibiting multiple disorders that affect ectodermal tissues. Over 150 different presentations of the syndrome have been reported, of which the most commonly encountered are hidrotic and hypohidrotic variants. In the present paper, we report the case of an 8-year-old male who was diagnosed with hypohidrotic ED by a physician. The extraoral and intraoral findings were recorded and found in accordance with the diagnosed variant. A comprehensive therapy was initiated which included child and parent counseling, familiarizing the child with dental setup, and delivery of a removable partial denture for the upper arch and a removable complete denture for the lower arch. The importance of follow-up and newer dentures as per the growth of the patient was also explained to the parents. The article highlights the key role of a pediatric dentist in managing the child and parents in syndromes as such.